Ocular Biometric and Optical Coherence Tomography Parameters in Former Preterm Children: A Cohort Study - Marzieh Najjaran; Siamak Zarei-Ghanavati; Hadi Ostadimoghaddam; Abbasali Yekta; Nasser Shoeibi; Armin Hemmati; Mojtaba Abrishami; Saeed Akhlaghi; Mohammed Ziaei (Journal of Ophthalmology)
Purpose. To compare biometric and optical coherence tomography parameters as well as refractive status in preterm children aged 4–8 years with or without retinopathy of prematurity (ROP), and evaluate their correlations with age and gender-matched full-term children. Methods. Retrospective comparative cohort study of four groups of children. Children with a history of preterm birth, including ROP who received intravitreal bevacizumab (IVB) treatment, children with a history of ROP that regressed without treatment and those with no history of ROP were compared to age and gender-matched full-term children as a control group. Best corrected visual acuity (BCVA), spherical equivalent of refraction (SE), macular and choroidal thickness, as well as biometric parameters was measured. Results. A total of 120 eyes of 120 children (30 children in each group) were included. There was no significant difference in BCVA, SE, and subjective cylinder between groups (p=0.05, p=0.3, p=0.6, respectively). Axial length was significantly shorter, and the cornea was steeper in both ROP groups than in other groups (p=0.001, p<0.001, respectively). The central macular thickness was significantly thicker in the treated, regressed ROP and preterm groups than in full-term children (p<0.001). The gestational age was negatively correlated with macular thickness in both treated and regressed ROP groups (r = −0.517; p=0.003, r = − 0.490; p=0.006, respectively). Conclusions. Children with a history of ROP had a shorter axial length, steeper cornea, and thicker macula that correlated with lower gestational age.